Seacoast Maine; people and places - Dibner, Martin; Tice, George A. (Garden City, N.Y., Doubleday, 1973)
A unique look at the people, the places and the many moods of Maine, portrayed in loving, insightful text and sensitive photographs. Martin Dibner and George A. Tice have recorded lobstermen, boatbuilders, quarry works and other long=time residents; they have roamed the woods and rocks and coast and here in an unforgettable portrait, they evoke those qualities that make Maine such a special place not only for Down Easters but for people all over America.
Island people -- Life in a seacoast village -- Creative people -- Man and the sea -- The predators -- The present past -- Taste of memory -- The Maine mystique -- What the earth holds -- People and places -- And how the weather was
Keywords: Maine -- Description and travel; Maine -- Social life and customs